Congenital renal dysplasia in a male goat- a case report - Imad Ibrahim Ali Al-Sultan; O.E.Ibrahim; M.Othman; A.R. Hassan (2011)
Renal dysplasia is a developmental or genetic defect of the kidneys. The incidence of unilateral renal dysplasia is quoted as very rare. It is more common in the males and affects the left side more often than the right. In our case, an apparently healthy 15 month-old goat was euthanized and dissected for the teaching of anatomy. It was discovered that the left kidney was not present but in its place was found an irregular mass of fibro-fatty tissue measuring 3.5cmx2.0cmx1.5cm. The ureter was also present, protruding from the left kidney mass. The right kidney was located in its proper place in the pelvis measuring 6.2cmx4.0cmx2.7cm. This right kidney appears to be bigger than the size of a normal kidney (5.3cmx3.5cmx1.8cm) in a goat of similar age. A histopathological section of the remains of the left kidney demonstrates very indistinct features of remnants of primitive underdeveloped renal structures with diffuse interstitial fibrosis. It is typical of a dysplastic kidney. The right kidney shows typical histological features of normal renal parenchyma, and appears to be hypertrophic. There were no other abnormalities detected in this case. This is the first such case reported from Kelantan, Malaysia.